Management of Intra-Uterine Growth Restriction by Ayurvedic Regime: A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Maternal nutrition and congenital malformation are considered as very important factors for intra uterine growth restriction. Present case deals with these two factors in parallel way. A 32 years young lady second gravida, G2P0A1, housewife, residence of Jaipur, came to NIA OPD with complaint of amenorrhea since a month. According to patient her last menstrual period was on 3/3/20. Her antenatal care was continued in NIA OPD. First fetal wellbeing scan reveals mild ventriculomegaly so she was advised for second level scan and quadruple marker but due to low socioeconomic condition patient was not able to do second level anomaly scan and she continued her pregnancy on her own risk. After 7 months she came to us with the complaints of decreased fetal movements. Fundal height corresponding to period of gestation and fetal heart sound was present which was regular. A color doppler was advised which shows normal fetoplacental and uteroplacental circulation, fetal weight was normal according to period of gestation. On the eighth month the fundal height was found decreased along with maternal weight decreased by 1kg. She was suspected for IUGR and planned for Ksheerbasti. After four episodes Ksheer basti on the 36 weeks of gestation, mother had significant weight gain of 2 kg along with increase in fundal height. USG was done which reveals Single live intra uterine pregnancy of 33 weeks 2 days with lumbar spina bifida with meningomyelocele, CHIARI-II brain malformation, EFW– 2282gm. She delivered a live female child of 2300gm through normal vaginal delivery at maternity hospital. Child was having severe form of myelomeningocele with brain malformation.